Fabrication of MWCNTs/ThO2 nanocomposite and its adsorption behavior for the removal of Pb(II) metal from aqueous medium. Issue 46 (1st October 2016) - Mittal, Alok; Naushad, Mu.; Sharma, Gaurav; ALothman, Z.A.; Wabaidur, S.M.; Alam, Manawwer
Abstract: Multiwall carbon nanotubes (MWCNTs) were chemically modified to form nanocomposite with thorium oxide. The MWCNTs/ThO2 nanocomposite was characterized using different modern techniques including Fourier transform infrared spectroscopy, X-ray powdered diffraction, scanning electron microscope, and transmission electron microscope. The average size of MWCNTs/ThO2 nanocomposite was in the range from 5 to 10 nm. The nanocomposite material was investigated for its adsorption behavior for Pb(II) ions removal from its aqueous system. For the adsorption of Pb(II) by MWCNTs/ThO2, the equilibrium was achieved within 50 min. The temperature and pH have also found to play important role in the adsorption process and maximum adsorption was found at 45°C and pH 5.5.